Voet's principles of biochemistry - Voet, Donald; Pratt, Charlotte W.; Voet, Judith G. (John Wiley & Sons, 2017)
While continuing in its tradition of presenting complete and balanced coverage, this Global Edition includes new pedagogy and enhanced visuals that provide a clear pathway for student learning. It provides a solid biochemical foundation that is rooted in chemistry to prepare students for the scientific challenges of the future. New information related to advances in biochemistry and experimental approaches for studying complex systems are introduced.